Compounds, methods of making and related products

CN122444781BActive Publication Date: 2026-10-27SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610894671.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-27
Estimated Expiration
2046-06-22

AI Technical Summary

Technical Problem

固态电解质虽具有较高的稳定性,但其与电极材料的界面接触较差,离子电导率较低,难以充分发挥高压实极片的容量优势

Benefits of technology

本申请化合物将磷酸酯基与氰基通过特定碳原子间隔连接于同一分子主链,并使磷酸酯基与氰基形成特定的空间构型。这种结构赋予该化合物较强的极性和配位能力,使其能够与过渡金属离子形成稳定的多元环状配合物,有效锚定正极活性颗粒表面的金属离子,抑制金属离子溶出和氧化电解质,为后续制备高性能聚合物材料提供了结构基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122444781B_ABST
    Figure CN122444781B_ABST
Patent Text Reader

Abstract

The application provides a compound and a preparation method thereof, a phosphate-based polymer, a pre-polymer liquid, a solid-state electrolyte, a secondary battery, and an electric device. The compound comprises a molecular structure as shown in the following formula I: wherein n1, n2 and n3 are each independently an integer from 1 to 3; R1, R2, R3, R4, R5 and R6 are each independently selected from a group as shown in the following formula II: wherein m is an integer from 1 to 3, and represents a connection site; and R7 is selected from H or a methyl group. The compound can improve the technical problems of the solid-state electrolyte in terms of the wettability of a high-compact electrode sheet and high-voltage resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, and specifically relates to a compound and its preparation method, a phosphate ester-based polymer, a prepolymer, a solid electrolyte, a secondary battery, and an electrical device. Background Technology

[0002] Lithium-ion batteries are widely used in consumer electronics. Increasing the compaction density and charging cutoff voltage of lithium cobalt oxide cathode sheets is a crucial technological approach to improving battery energy density and range. Currently, the industry has achieved a relatively high compaction density for lithium cobalt oxide cathode sheets and raised their charging cutoff voltage to 4.6V.

[0003] However, traditional liquid electrolytes have high viscosity, making it difficult to fully wet high-pressure solid electrodes with small pore size and low porosity, which hinders ion transport and affects the cycle life of the battery.

[0004] To address these issues, researchers have attempted to develop solid-state electrolytes to replace traditional liquid electrolytes. While solid-state electrolytes offer higher stability, their interfacial contact with electrode materials is poor, resulting in lower ionic conductivity and hindering the full utilization of the capacity advantages of high-voltage solid electrodes.

[0005] However, how to design the molecular structure of compounds to enable solid electrolytes to simultaneously achieve good wettability to high-voltage solid electrodes and withstand high voltage remains a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] This application provides a compound and its preparation method, a phosphate ester-based polymer, a prepolymer, a solid electrolyte, a secondary battery, and an electrical device, aiming to solve the technical problem of achieving good wettability to high-voltage solid electrodes and high voltage tolerance.

[0007] In a first aspect, embodiments of this application provide a compound comprising a molecular structure as shown in Formula I: Formula I; Where n1, n2, and n3 are each an independent integer from 1 to 3; R1, R2, R3, R4, R5, and R6 are each independently selected from the groups shown in Formula II: Formula II, m takes the value of an integer from 1 to 3. Indicates the connection site; R7 is selected from H or methyl.

[0008] Optionally, in some embodiments of this application, the compound is selected from one or more of the following chemical formulas:

[0009] .

[0010] Optionally, in some embodiments of this application, the compound is used as a polymer monomer to prepare a polymer solid electrolyte.

[0011] Secondly, embodiments of this application also provide a method for preparing the aforementioned compound, the method comprising: The first precursor is obtained by reacting a polyol compound with an acrylic acid compound. The first precursor is reacted with phosphorous acid to obtain the second precursor; The second precursor was subjected to a nucleophilic substitution reaction with an alkali metal alkoxide to obtain an intermediate product. The intermediate product was reacted with a haloacetonitrile compound to obtain the compound; The polyol compound is selected from polyols having at least four hydroxyl groups, and the acrylic compound is selected from acrylic acid.

[0012] Thirdly, embodiments of this application also provide a phosphate ester-based polymer, wherein the compound polymerized to form the phosphate ester-based polymer includes the compounds described above, or compounds prepared by the preparation methods described above.

[0013] Fourthly, embodiments of this application also provide a prepolymer liquid, the prepolymer liquid comprising a lithium salt, a solvent, and a polymer monomer, the polymer monomer comprising a molecular structure as shown in Formula I: Formula I; Where n1, n2, and n3 are each an independent integer from 1 to 3; R1, R2, R3, R4, R5, and R6 are each independently selected from the groups shown in Formula II: Formula II, m takes the value of an integer from 1 to 3. Indicates the connection site; R7 is selected from H or methyl.

[0014] Optionally, in some embodiments of this application, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium difluorophosphate.

[0015] Optionally, in some embodiments of this application, the solvent includes at least one of carbonate solvents and carboxylic acid ester solvents.

[0016] Optionally, in some embodiments of this application, the additive includes at least one of propane sulpholactone, vinyl sulfate, and 1,3,6-hexanetrionitrile.

[0017] Optionally, in some embodiments of this application, the prepolymer liquid further includes an initiator and / or additives; wherein the additives include at least one selected from propane sulpholactone, vinyl sulfate, and 1,3,6-hexanetrionitrile.

[0018] Optionally, in some embodiments of this application, the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and azobiscyclohexylformitrile.

[0019] Optionally, in some embodiments of this application, the mass fraction of the compound in the prepolymer liquid ranges from 1% to 5%.

[0020] Optionally, in some embodiments of this application, the mass fraction of the lithium salt in the prepolymer liquid ranges from 10% to 20%.

[0021] Optionally, in some embodiments of this application, the solvent accounts for a mass fraction of 75% to 87% of the prepolymer liquid.

[0022] Optionally, in some embodiments of this application, the additive accounts for a mass fraction of 1% to 5% of the prepolymer liquid.

[0023] Optionally, in some embodiments of this application, the mass ratio of the initiator to the compound is 0.003 to 0.03.

[0024] Fifthly, embodiments of this application also provide a solid electrolyte, which is formed by curing the prepolymer as described above.

[0025] Sixthly, embodiments of this application also provide a secondary battery, the secondary battery comprising: a positive electrode; a negative electrode and a solid electrolyte located between the positive electrode and the negative electrode, the solid electrolyte being formed by curing a prepolymer liquid as described above.

[0026] Optionally, in some embodiments of this application, the positive electrode comprises lithium cobalt oxide.

[0027] Optionally, in some embodiments of this application, the compaction density of the positive electrode sheet ranges from 4.1 g / cm³. 3 Up to 4.4 g / cm 3 .

[0028] In a seventh aspect, embodiments of this application also provide an electrical device comprising at least a solid electrolyte as described above, or a secondary battery as described above.

[0029] The beneficial effects of the embodiments of this application are as follows: The compound of this application links phosphate ester groups and cyano groups to the same molecular backbone through specific carbon atom spacing, and forms a specific spatial configuration between the phosphate ester groups and cyano groups. This structure endows the compound with strong polarity and coordination ability, enabling it to form stable multi-cyclic complexes with transition metal ions, effectively anchoring metal ions on the surface of positive electrode active particles, inhibiting metal ion dissolution and electrolyte oxidation, and providing a structural basis for the subsequent preparation of high-performance polymer materials.

[0030] The method described in this application employs a four-step synthetic route: esterification of a polyol compound with acrylate, reaction with phosphorous acid, nucleophilic substitution with an alkali metal alkoxide, and reaction with a haloacetonitrile compound. This method utilizes readily available raw materials, operates under mild conditions, and is simple to perform, enabling efficient production of the target compound and making it suitable for industrial-scale manufacturing.

[0031] Phosphate ester polymers inherit the structural characteristics of the compound, with phosphate ester and cyano groups uniformly distributed in their molecular chains. These polar groups can coordinate and complex with transition metal ions. Simultaneously, the phosphorus-oxygen double bond of the phosphate ester group and the carbon-nitrogen triple bond of the cyano group possess strong chemical bond energies, endowing the polymer backbone with excellent high-voltage resistance. The polymer network has a moderate crosslinking density and suitable elasticity, enabling it to adapt to the volume expansion during electrode charging and discharging, preventing cracks and interfacial delamination, while maintaining good ion conduction pathways.

[0032] The polymer in this application has a specific molecular structure, and the resulting solid electrolyte can effectively wet the pores of the high-voltage solid electrode, forming a good interfacial contact with the electrode material, while also exhibiting good stability and ionic conductivity. This solid electrolyte can suppress oxidative decomposition reactions under high voltage, reduce side reactions, and improve electrochemical stability.

[0033] The solid electrolyte preparation method of this application involves mixing the aforementioned compound with lithium salt and organic solvent to form a prepolymer solution, followed by in-situ crosslinking reaction to prepare the solid electrolyte. This preparation process is simple and can achieve integrated molding of the electrolyte and electrode. The prepolymer solution solidifies in-situ inside the battery to form a solid electrolyte, which can fully fill the pores of the electrode, improve the interfacial contact between the electrolyte and the electrode, and reduce the interfacial impedance.

[0034] The solid electrolyte of this application has good high-voltage solid electrode wettability and high voltage stability. The secondary battery prepared by it can operate stably at a high voltage of 4.6V, giving full play to the capacity advantage of lithium cobalt oxide cathode material, while maintaining excellent cycle stability.

[0035] The electrical equipment used in this application has higher discharge capacity and higher stability, which can meet the requirements of consumer electronics products for cycle stability. Attached Figure Description

[0036] To more clearly illustrate the solutions in this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0037] Figure 1 The infrared spectrum of the compound prepared in Example 1 of this application is shown.

[0038] Figure 2 This is a comparison chart of the liquid absorption test results of the soft-pack full battery in Example 1 and Comparative Example 1 of this application.

[0039] Figure 3 This is a comparison chart of the high-voltage cycling curves of solid-state pouch cells in Example 1 and Comparative Example 1 of this application. Detailed Implementation

[0040] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. In addition, it should be understood that the specific embodiments described herein are only for illustration and explanation of this application and are not intended to limit this application. In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in actual use or operation, specifically the drawing directions in the accompanying drawings; while "inner" and "outer" refer to the outline of the device.

[0041] In a first aspect, embodiments of this application provide a compound comprising a molecular structure as shown in Formula I: Formula I; where n1, n2, and n3 are each independently an integer from 1 to 3; R1, R2, R3, R4, R5, and R6 are each independently selected from the groups shown in Formula II: In Equation II, m takes the value of an integer from 1 to 3. Indicates the linking site; R7 is selected from H or methyl.

[0042] Understandably, this compound connects phosphate ester groups and cyano groups on the same molecular backbone through specific carbon atom spacing, and forms a specific spatial configuration between the phosphate ester groups and cyano groups. This structure endows the compound with strong polarity and coordination ability, enabling it to form stable multi-cyclic complexes with transition metal ions, effectively anchoring metal ions on the surface of positive electrode active particles, inhibiting metal ion dissolution and electrolyte oxidation, and providing a structural basis for the subsequent preparation of high-performance polymer materials.

[0043] Specifically, the functionality of the compound in this application is 6. Functionality refers to the number of functional groups in a compound molecule that can participate in the reaction, and it is directly related to the reactivity of the reactants and the structural characteristics of the products. Functionality determines the number of active sites in the compound molecule during the reaction, thus affecting the reaction rate and reaction pathway. Generally speaking, the higher the functionality, the more active sites the compound molecule has in the reaction, the faster the reaction rate may be, and the greater the probability that the compound molecule will participate in the polymerization reaction and chain growth, meaning that the compound can be more fully transformed into the polymer network backbone.

[0044] In some embodiments, the compound is selected from one or more of the following chemical formulas:

[0045] .

[0046] It is understandable that R1–R6 in the compounds of formulas 1 to 7 are selected from the groups shown in formula II, and the length and flexibility of the side chains can be adjusted by controlling the value of m. This structural design enables the polymer network formed after polymerization to have moderate chain segment mobility, which is beneficial for the uniform and efficient transport of lithium ions in the polymer electrolyte, while maintaining the integrity of the network and reducing the local aggregation of lithium ions.

[0047] In some embodiments, the compound is used as a polymer monomer to prepare a polymer solid electrolyte.

[0048] Secondly, embodiments of this application also provide a method for preparing the aforementioned compound, the method comprising: S100: A polyol compound is reacted with an acrylic acid compound to obtain the first precursor; S200: The first precursor is reacted with phosphorous acid to obtain the second precursor; S300: The second precursor is subjected to a nucleophilic substitution reaction with an alkali metal alkoxide to obtain an intermediate product; S400: The intermediate product is reacted with a haloacetonitrile compound to obtain the compound; The polyol compound is selected from polyols having at least four hydroxyl groups, and the acrylic compound is selected from acrylic acid.

[0049] It is understood that the preparation method of this application employs a four-step synthetic route: esterification of a polyol compound with an acrylic acid compound, reaction with phosphorous acid, nucleophilic substitution with an alkali metal alkoxide, and reaction with a haloacetonitrile compound. This preparation method uses readily available raw materials, operates under mild conditions, and is simple to operate, enabling efficient acquisition of the target compound and making it suitable for industrial production.

[0050] Specifically, in S100, the molar ratio of the polyol compound to the acrylic acid compound is 1:3; in step 200, the molar ratio of the first precursor to phosphorous acid is 2:1; in step 300, the molar ratio of the second precursor to the alkali metal alkoxide is 1:1; and in step 400, the molar ratio of the intermediate product to the haloacetonitrile compound is 1:1.

[0051] Thirdly, embodiments of this application also provide a phosphate ester-based polymer, wherein the compound polymerized to form the phosphate ester-based polymer includes the compounds described above, or compounds prepared by the preparation methods described above.

[0052] Understandably, phosphate ester polymers inherit the structural characteristics of their compounds, with phosphate ester and cyano groups uniformly distributed throughout their molecular chains. These polar groups can coordinate and complex with transition metal ions. Simultaneously, the phosphorus-oxygen double bond of the phosphate ester group and the carbon-nitrogen triple bond of the cyano group possess strong chemical bond energies, endowing the polymer backbone with excellent high-voltage resistance. The polymer network exhibits a moderate crosslinking density and suitable elasticity, enabling it to adapt to the volume expansion during electrode charging and discharging, preventing cracks and interfacial delamination, while maintaining good ion conduction pathways.

[0053] In some embodiments, the conditions for polymerizing the compounds of this application to form phosphate ester-based polymers include: an in-situ thermosetting temperature ranging from 45°C to 90°C, and an in-situ thermosetting time ranging from 5 hours to 50 hours. The in-situ thermosetting temperature range includes any value or a range of any two of the following: 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, and 90°C. The in-situ thermosetting time range includes any value or a range of any two of the following: 5 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, 48 ​​hours, and 50 hours.

[0054] Fourthly, embodiments of this application also provide a prepolymer liquid, the prepolymer liquid comprising a lithium salt, a solvent, and a polymer monomer, the polymer monomer comprising a molecular structure as shown in Formula I: Formula I; where n1, n2, and n3 are each independently an integer from 1 to 3; R1, R2, R3, R4, R5, and R6 are each independently selected from the groups shown in Formula II: In Equation II, m takes the value of an integer from 1 to 3. Indicates the linking site; R7 is selected from H or methyl.

[0055] Understandably, the aforementioned polymer monomer is mixed with lithium salt and solvent to form a prepolymer solution, which is then used to prepare a solid electrolyte through an in-situ crosslinking reaction. This preparation process is simple and enables the integrated molding of the electrolyte and electrode. The prepolymer solution solidifies in-situ inside the battery to form a solid electrolyte, which can fully fill the pores of the electrode, improve the interfacial contact between the electrolyte and the electrode, and reduce the interfacial impedance.

[0056] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium difluorophosphate.

[0057] In some embodiments, the solvent includes at least one of carbonate solvents and carboxylic acid ester solvents.

[0058] Understandably, specific types of lithium salts and additives are introduced into this solid electrolyte. These components, in synergy with the phosphate ester-based polymer, further optimize the electrolyte's ion conductivity and interfacial stability. Lithium salts such as lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium difluorophosphate provide a sufficient source of lithium ions, while carbonate and carboxylic acid ester solvents provide good solubility and low viscosity, ensuring sufficient wetting of the prepolymer in the high-voltage solid electrode. Simultaneously, the phosphate ester-based polymer in this solid electrolyte exhibits good compatibility with solvents and lithium salts, avoiding stability issues such as phase separation, layering, and excessive liquid precipitation.

[0059] In some embodiments, the prepolymer solution further includes an initiator and / or additives; wherein the additives include at least one selected from propane sulpholactone, vinyl sulfate, and 1,3,6-hexanetrionitrile.

[0060] In some embodiments, the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and azobiscyclohexylformitrile.

[0061] Understandably, this prepolymer solution also contains specific types of initiators and additives. Azo initiators can initiate polymerization reactions under heating conditions to form a stable three-dimensional network structure; additives such as propane sulpholactone, vinyl sulfate, and 1,3,6-hexanetrionitrile can form a stable interfacial film on the electrode surface, further optimizing interfacial properties and enhancing the high-voltage withstand capability of the electrolyte. The synergistic effect of these components makes the preparation process easier to control, resulting in a solid electrolyte with superior performance.

[0062] In some embodiments, the mass fraction of the compound in the prepolymer liquid ranges from 1% to 5%.

[0063] In some embodiments, the mass fraction of the lithium salt in the prepolymer liquid ranges from 10% to 20%.

[0064] In some embodiments, the solvent accounts for 75% to 87% of the mass fraction of the prepolymer liquid.

[0065] In some embodiments, the additive accounts for a mass fraction of 1% to 5% of the prepolymer solution.

[0066] In some embodiments, the mass ratio of the initiator to the compound is 0.003 to 0.03. The mass fraction of the initiator in the prepolymer solution ranges from 0.003% to 0.15%.

[0067] Understandably, this method controls the content of each component within a specific range. A compound content of 1% to 5% ensures the formation of a moderately cross-linked network structure, maintaining high ionic conductivity while ensuring the mechanical strength of the gel electrolyte; a lithium salt content of 10% to 20% provides sufficient carrier concentration to meet the lithium-ion conduction requirements during battery charging and discharging; a solvent content of 75% to 87% ensures suitable fluidity and wettability of the prepolymer solution, allowing it to fully penetrate the micropores of the high-voltage solid electrode; an additive content of 1% to 5% effectively optimizes electrode interface performance and suppresses side reactions; and a mass ratio of initiator to compound of 0.003 to 0.03 ensures a stable polymerization reaction, avoiding either excessively rapid reaction leading to structural inhomogeneity or excessively slow reaction leading to incomplete curing. Through the synergistic control of the component content, a solid electrolyte exhibiting excellent overall performance in terms of wettability, mechanical strength, and high voltage stability can be obtained. The mass fraction of the compound in the prepolymer solution ranges from 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, and 5%, or any combination thereof. The mass fraction of the lithium salt in the prepolymer solution ranges from 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, and 20%, or any combination thereof. The solvent, as the balance component, must have a mass fraction that meets the requirement that the total composition is 100%. The solvent's mass fraction in the prepolymer liquid can be any value from 75.0%, 75.5%, 76.0%, 76.5%, 77.0%, 77.5%, 78.0%, 78.5%, 79.0%, 79.5%, 80.0%, 80.5%, 81.0%, 81.5%, 82.0%, 82.5%, 83.0%, 83.5%, 84.0%, 84.5%, 85.0%, 85.5%, 86.0%, 86.5%, and 87.0%, or any combination thereof. The additive's mass fraction in the prepolymer liquid can be any value from 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%, or any combination thereof. The mass ratio of the initiator to the compound can be any value from 0.003, 0.005, 0.007, 0.009, 0.012, 0.015, 0.018, 0.021, 0.024, 0.027, 0.03, or a range of any two of these values.The mass fraction of the initiator in the prepolymer liquid can be any value or a range of any two of the following: 0.003%, 0.006%, 0.009%, 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.12%, 0.14%, and 0.15%.

[0068] Fifthly, embodiments of this application also provide a solid electrolyte, which is formed by curing the prepolymer as described above.

[0069] It is understood that the polymer of this application has a specific molecular structure, and the resulting solid electrolyte can effectively wet the pores of the high-voltage solid electrode, forming a good interfacial contact with the electrode material, while maintaining stability and ionic conductivity. This solid electrolyte can suppress oxidative decomposition reactions under high voltage, reduce side reactions, and improve electrochemical stability.

[0070] Sixthly, embodiments of this application also provide a secondary battery, the secondary battery comprising: a positive electrode; a negative electrode and a solid electrolyte located between the positive electrode and the negative electrode, the solid electrolyte being formed by curing a prepolymer liquid as described above.

[0071] Conventional electrolytes are prone to oxidative decomposition on the positive electrode surface under high voltages of 4.6V, forming an unstable interface layer, which exacerbates gas generation reactions and increases impedance, severely restricting battery stability. Existing liquid electrolyte materials are insufficient to meet the application requirements of high-compaction, high-voltage electrodes.

[0072] Understandably, because the solid electrolyte of this application has good high-voltage solid electrode wettability and high voltage stability, the prepared secondary battery can operate stably at a high voltage of 4.6V, giving full play to the capacity advantage of lithium cobalt oxide cathode material, while maintaining excellent cycle stability.

[0073] In some embodiments, the positive electrode comprises lithium cobalt oxide.

[0074] It is understandable that the lithium cobalt oxide cathode has good compatibility with the solid electrolyte of this application, and the phosphate ester groups and cyano groups in the solid electrolyte can react with the Co groups formed by lithium cobalt oxide under high voltage. 4+ Synergistic complexation occurs, anchoring cobalt ions to the surface of the positive electrode active particles, stabilizing the positive electrode interface, and preventing cobalt dissolution and electrolyte oxidation. The combination of these two factors can fully leverage the high voltage capacity advantage of lithium cobalt oxide.

[0075] In some embodiments, the positive electrode sheet, based on its mass fraction, comprises lithium cobalt oxide ranging from 94% to 98%, a conductive agent ranging from 1% to 5%, and a binder ranging from 1% to 5%.

[0076] It is understood that the positive electrode slurry contains lithium cobalt oxide, conductive agents, binders, and solvents, which are used for mixing, dispersing, and adjusting the slurry viscosity. These components volatilize during drying and are therefore not included in the mass percentage of the positive electrode sheet. The mass fraction of lithium cobalt oxide in the positive electrode sheet ranges from any value or a range of two of the following: 94.0%, 94.2%, 94.4%, 94.6%, 94.8%, 95.0%, 95.2%, 95.4%, 95.6%, 95.8%, 96.0%, 96.2%, 96.4%, 96.6%, 96.8%, 97.0%, 97.2%, 97.4%, 97.6%, 97.8%, and 98.0%. The mass fraction of the conductive agent in the positive electrode sheet includes any value or a range of any two of the following: 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, and 5.0%. The mass fraction of the binder in the positive electrode sheet includes any value or a range of any two of the following: 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, and 5.0%.

[0077] In some examples, the conductive agent includes acetylene black, but is not limited to this.

[0078] In some examples, the adhesive includes polyvinylidene fluoride, but is not limited to this.

[0079] In some embodiments, the compaction density of the positive electrode sheet ranges from 4.1 g / cm³. 3 Up to 4.4 g / cm 3 .

[0080] Understandably, the compaction density of the positive electrode sheet in this application is controlled within the range of 4.1 g / cm³ to 4.4 g / cm³. Within this compaction density range, the aforementioned solid electrolyte can effectively wet the pores of the electrode sheet, forming a good ion conduction pathway, allowing the capacity of the active material to be fully utilized. Simultaneously, the gel network formed by the solid electrolyte possesses appropriate elasticity and strength, enabling it to adapt to the volume expansion and contraction of the electrode sheet during charging and discharging, maintaining good interfacial contact.

[0081] In some embodiments, the negative electrode sheet is prepared according to the following steps: graphite and silicon particles are mixed uniformly at a mass ratio of 8:2 to obtain a silicon-carbon composite negative electrode material; then, 80% to 95% of the silicon-carbon composite negative electrode material is added to 1% to 10% of conductive carbon black (SP), and the mixture is ground and mixed; then, 1% to 5% of sodium carboxymethyl cellulose (CMC), 1% to 5% of polystyrene-butadiene copolymer (SBR), and water are added, and the mixture is ground, dispersed, and mixed; the mixture is then coated onto the surface of copper foil, dried, and the negative electrode sheet is obtained; after rolling, the compacted density is 1.7 g / cm³. 3 The diaphragm is a porous support material that isolates the positive and negative electrodes. It can be made of polyethylene diaphragm, polypropylene diaphragm, polytetrafluoroethylene nonwoven fabric, etc.

[0082] In a seventh aspect, embodiments of this application also provide an electrical device, the electrical device including the solid electrolyte including the solid electrolyte as described above, or the secondary battery as described above.

[0083] It is understandable that the electrical equipment used in this application has higher discharge capacity and higher stability, which can meet the requirements of consumer electronics products for cycle stability.

[0084] The present application will be further described below through specific embodiments. Unless otherwise specified, the experimental materials used in the embodiments can be purchased from conventional biochemical reagent companies.

[0085] Example 1 The compound was prepared according to the following steps: Step 1: 1 mol of 2,2-dihydroxymethyl-1,3-propanediol and 3 mol of acrylic acid were stirred evenly, and 0.01 mol of dibutyltin dilaurate was added as a catalyst. The mixture was stirred at 60 °C for 6 h to obtain precursor 1. Step 2: 1 mol of precursor 1 and 0.5 mol of phosphorous acid were stirred evenly, and 0.01 mol of p-toluenesulfonic acid was added as a catalyst. The mixture was heated to 60°C and refluxed for 5 h under nitrogen protection. The generated water was removed through a water separator. After the reaction was completed, the acidic catalyst was neutralized with sodium carbonate solution. The organic phase was washed with water, dried with anhydrous sodium sulfate, and purified by vacuum distillation to obtain precursor 2. Step 3: Dissolve precursor 2 in N,N-dimethylformamide, then add sodium ethoxide dropwise, and stir at room temperature for 1 hour. The molar ratio of precursor 2 to sodium ethoxide is 1:1. Step 4: Add chloroacetonitrile, with a molar ratio of precursor 2 to chloroacetonitrile of 1:1. React at 60°C for 3 hours. Add the reaction product to deionized water, extract with ethyl acetate, wash the ethyl acetate organic phase with water, wash three times with deionized water, dry, filter, and distill under reduced pressure to obtain the compound. Figure 1 As shown, Figure 1 The infrared spectrum of the compound prepared in Example 1 is shown at 2250 cm⁻¹. -1 1721cm -1 1176cm -1 1263cm -1 3000cm -1 2904cm -1 The peaks observed correspond to the bending vibration peaks of the cyano group, acrylate group, phosphorus-oxygen double bond, stretching vibration peaks of the phosphorus-oxygen double bond, carbon-carbon double bond, and carbon-hydrogen bond, indicating that the obtained compound is the compound of formula 1. Specifically, n1, n2, and n3 are all 1, R1, R2, R3, R4, R5, and R6 are acrylates, m is 1, and R7 is H. The specific chemical structural formula is as follows: Formula 1.

[0086] Prepare the prepolymer solution according to the following steps: Step 5: Dissolve 3g of the compound prepared in this example and 0.03g of azobisisobutyronitrile in 96.97g of electrolyte to obtain a prepolymer solution; wherein the electrolyte solution includes: 39.97g of propyl propionate, 12g of methyl ethyl carbonate, 14g of ethylene carbonate, 11g of fluoroethylene carbonate, 1g of propane sulpholol, 1g of ethylene sulfate, 2g of 1,3,6-hexanetrionitrile, 12g of lithium hexafluorophosphate, 3g of lithium difluorosulfonylimide, and 1g of lithium difluorophosphate; Prepare the positive electrode sheet according to the following steps: Step 6: Grind and mix 98% (by mass) lithium cobalt oxide material and 1% (by mass) conductive agent acetylene black, add 1% (by mass) polyvinylidene fluoride (PVDF), and grind and disperse in 1-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. NMP is used for mixing, dispersing, and adjusting the slurry viscosity; it volatilizes during drying and is therefore not included in the mass percentage of the positive electrode material. Coat the positive electrode material onto the surface of aluminum foil, dry to obtain a positive electrode sheet, and roll-press it to a compaction density of 4.3 g / cm³. 3 .

[0087] Prepare the negative electrode sheet according to the following steps: Step 7: Mix graphite and silicon particles at a mass ratio of 8:2 to obtain a silicon-carbon composite anode material. Then, add 94.9% (by mass) of the silicon-carbon composite anode material to 1.2% (by mass) of conductive carbon black (SP), grind and mix. Add 1.5% (by mass) of sodium carboxymethyl cellulose (CMC), 2.4% (by mass) of polystyrene-butadiene copolymer (SBR), and water, grind and disperse, coat the mixture onto a copper foil surface, and dry to obtain the anode sheet. After rolling, the compacted density is 1.7 g / cm³. 3 The diaphragm is a porous support material that isolates the positive and negative electrodes, and is made of polyethylene.

[0088] Solid-state batteries are prepared according to the following steps: Step 8: In a drying room (relative humidity below 2%, dew point below -40ºC) at room temperature, inject the prepolymer solution into a dry cell assembled from a positive electrode, a negative electrode, and a separator, wherein the compaction density of the positive electrode is 4.3 g / cm³. 3 The prepolymer is pre-sealed using a heat sealer, left to stand at room temperature for 24 hours, and then placed in a hot oven and slowly heated to 50°C for 24 hours. During heating, the prepolymer solution undergoes a curing reaction inside the dry cell, and a solid electrolyte is obtained through in-situ thermal curing, thus forming a lithium-ion solid-state battery.

[0089] Example 2 The difference between this embodiment and Example 1 is that n1 and n3 are 2, that is, 2,2-dihydroxymethyl-1,3-propanediol in step 1 is replaced with 2,2-dihydroxymethyl-1,4-butanediol. The rest is the same as in Example 1. The specific chemical structural formula is: Formula 2.

[0090] Example 3 The difference between this embodiment and Example 1 is that n1 and n3 are 3, that is, 2,2-dihydroxymethyl-1,3-propanediol in step 1 is replaced with 2,2-dihydroxymethyl-1,5-pentanediol. The rest is the same as in Example 1. The specific chemical structural formula is: Formula 3.

[0091] Example 4 The difference between this embodiment and Example 1 is that n2=2, meaning that chloroacetonitrile in step 4 is replaced with chloropropionitrile. Everything else is the same as in Example 1. The specific chemical structural formula is: Formula 4.

[0092] Example 5 The difference between this embodiment and Example 1 is that R7 is methyl, meaning that chloroacetonitrile in step 4 is replaced with 2-chloropropionitrile. The rest is the same as in Example 1. The specific chemical structural formula is: Formula 5.

[0093] Example 6 The difference between this embodiment and Example 1 is that m=3, meaning that 2,2-dihydroxymethyl-1,3-propanediol in step 1 is replaced with 4-hydroxymethyl-4-hydroxypropyl-1,7-heptanediol. The rest is the same as in Example 1. The specific chemical structural formula is: Formula 6.

[0094] Example 7 The difference between this embodiment and Example 1 is that m=2, that is, 2,2-bis(hydroxymethyl)-1,3-propanediol in step 1 is replaced with 3-hydroxymethyl-3-hydroxyethyl-1,5-pentanediol. The rest is the same as in Example 1. The specific chemical structural formula is: Formula 7.

[0095] Example 8 The difference between this embodiment and Example 1 is that the compound accounts for 0.5% of the mass fraction of the prepolymer solution. Everything else is the same as in Example 1.

[0096] Example 9 The difference between this embodiment and Example 1 is that the compound accounts for 1% of the mass fraction of the prepolymer solution. The rest is the same as in Example 1.

[0097] Example 10 The difference between this embodiment and Example 1 is that the compound accounts for 5% of the mass fraction of the prepolymer solution. The rest is the same as in Example 1.

[0098] Example 11 The difference between this embodiment and Example 1 is that the compound accounts for 6% of the mass fraction of the prepolymer solution. Everything else is the same as in Example 1.

[0099] Example 12 The difference between this embodiment and Example 1 is that the mass ratio of initiator to compound is 0.002. Everything else is the same as in Example 1.

[0100] Example 13 The difference between this embodiment and Example 1 is that the mass ratio of the initiator to the compound is 0.003. Everything else is the same as in Example 1.

[0101] Example 14 The difference between this embodiment and Example 1 is that the mass ratio of initiator to compound is 0.03. Everything else is the same as in Example 1.

[0102] Example 15 The difference between this embodiment and Example 1 is that the mass ratio of initiator to compound is 0.04. Everything else is the same as in Example 1.

[0103] Example 16 The difference between this embodiment and Embodiment 1 is that the compaction density of the positive electrode sheet of the battery cell injected with the prepolymer liquid is 4.4 g / cm³. 3 .

[0104] Example 17 The difference between this embodiment and Embodiment 1 is that the compaction density of the positive electrode sheet of the battery cell injected with the prepolymer solution is 4.5 g / cm³. 3 .

[0105] Comparative Example 1 The difference between this comparative example and Example 1 is that the main chain of compound D1 lacks phosphorus-oxygen double bonds. Its specific structure is shown below, where n1, n2, and n3 are 1, R1, R2, R3, R4, R5, and R6 are acrylates, and R7 is H, the same as in Example 1. The rest is also the same as in Example 1. The specific chemical structural formula is: D1.

[0106] Comparative Example 2 The difference between this comparative example and Example 1 is that compound D2 has no carbon-nitrogen triple bonds in its main chain, and its specific structure is shown below. Everything else is the same as in Example 1. The specific chemical structural formula is: D2.

[0107] Comparative Example 3 The difference between this comparative example and Example 1 is that compound D3 lacks phosphorus-oxygen double bonds and carbon-nitrogen triple bonds in its main chain, as shown in the following structure. Everything else is the same as in Example 1. The specific chemical structural formula is: D3.

[0108] Comparative Example 4 The difference between this comparative example and Example 1 is that the functionality is 4, meaning that R1, R2, R3, R4, R5, and R6 contain two hydroxymethyl groups and four acrylate groups. The rest is the same as in Example 1. The specific chemical structural formula is as follows: D4.

[0109] Comparative Example 5 The difference between this comparative example and Example 1 is that the functionality is 2, meaning that R1, R2, R3, R4, R5, and R6 contain four hydroxymethyl groups and two acrylate groups. The rest is the same as in Example 1. The specific chemical structural formula is as follows: D5.

[0110] Comparative Example 6 The difference between this comparative example and Example 1 is that n1, n2, and n3 are 0; the rest are the same as in Example 1. The specific chemical structural formula is: D6.

[0111] Comparative Example 7 The difference between this comparative example and Example 1 is that n1, n2, and n3 are 4; the rest are the same as in Example 1. The specific chemical structural formula is: D7.

[0112] Comparative Example 8 The difference between this comparative example and Example 1 is that the compound is a mixture of compounds D1 and D2, i.e., the phosphorus-oxygen double bond and carbon-nitrogen triple bond each correspond to different compounds and are not on the same molecular structure. The content of D1 and D2 is 1.5% each, totaling 3%. Everything else is the same as in Example 1.

[0113] Test methods Material testing methods Infrared spectroscopy test: Place the sample to be tested on the crystal surface of the optical platform of the ATR (model is20) infrared spectrometer. Open the infrared ATR testing software and set the test parameters: resolution 4 and scan count 32. After starting the instrument, rotate the knob above the reflector to press the sample into full contact with the emission aperture below, and begin data acquisition. After the test is completed, the infrared spectral information of the sample can be obtained.

[0114] Viscosity test: The viscosity of the organic solid electrolyte prepolymer solution was tested using an NDJ-5S digital rotary viscometer. The prepolymer solution was poured into a flat-bottomed container with a diameter greater than 60 mm. The prepolymer solution temperature was maintained at 25°C, and the operating surface was stable and vibration-free. The instrument protective bracket was screwed into the lower end of the instrument in reverse. Using the L0 rotor, it was screwed counterclockwise into the universal joint. The lifting knob was rotated to slowly immerse the rotor in the prepolymer solution until the rotor's liquid level mark (the groove scale) was flush with the liquid surface. The instrument was then leveled again. The rotor selection key was pressed to select the rotation speed, and then the OK key was pressed. The rotor began to rotate. After the displayed value stabilized, the stop key was pressed to read the viscosity value.

[0115] Cell liquid absorption test: Hang the dry cell under the balance and slowly place it into the transparent experimental groove (20cm long, 10cm wide, and 20cm high). The groove is pre-filled with the electrolyte solution to be tested, with the liquid level at half the height of the groove, i.e., 10cm. The bottom of the cell should be in contact with the electrolyte solution, and the liquid level should be 1mm higher than the bottom of the cell. Record the time and the balance reading as the starting point of the immersion experiment. Record the change in the mass of the cell weighed by the balance after 6 hours.

[0116] Electrochemical stability window test: A stainless steel sheet was placed in the CR2016 battery casing, and the prepolymer sample of this application was dropped in. The lithium sheet and battery casing were then covered and clamped together. The CR2016 button battery was assembled in a glove box filled with high-purity argon gas. Four batteries were prepared for each sample group. The sample was heated to 50°C and reacted for 24 hours. The electrochemical stability window was measured by linear voltammetry using an electrochemical workstation (BioLogic Science Instruments). The initial potential was 2.5 V, the highest potential was 6 V, and the scan rate was 10 mV / s. The voltage value corresponding to the intersection of the tangent line of the current slope increase region and the horizontal axis in the curve was read as the high-voltage withstand window.

[0117] Young's modulus test: Turn on the Mettler DMA850 instrument, select the constant strain test compression mode, use a titanium alloy compression test stage with a diameter of 10 mm, cut out a cylindrical organic solid electrolyte sample with a diameter of 6 mm and a height of 2 mm, test temperature 25℃, test frequency 1 Hz, constant compression of 10 μm, initial stroke compression of 15 μm, continue for 10 min, use DMA instrument software to collect test data, take the data of the last 5 min, test at least 3 parallel samples for each batch of samples, calculate the average value as the output result, and obtain the Young's modulus.

[0118] Conductivity test: The electrode rings that hold the electrolyte container and the PTFE single ring that serves as the electrolyte container are placed at the bottom of the battery casing. The prepolymer solution to be tested is then dropped into the electrolyte container, ensuring the electrolyte completely fills the chamber. A stainless steel electrode plug is then placed on top, forming the blocking electrode. Finally, the battery casing cover is placed on top, and the wing nut is tightened to complete the battery assembly. The assembled blocking battery is directly connected to an electrochemical workstation (VMP-3e, Bio-Logic) and placed in a 50°C constant temperature chamber for high-temperature curing. AC impedance testing is performed at frequencies from 1 MHz to 0.03 Hz, and EIS testing is also conducted. The ionic conductivity (σ, mS / cm) of the solid electrolyte is calculated using the formula σ = L / (R*S), where σ is the ionic conductivity, L is the electrolyte thickness, S is the contact area between the electrolyte membrane and the electrode, and R is the impedance measured by the impedance meter.

[0119] Battery testing methods High-voltage cycle testing of solid-state pouch cell full batteries: (1) The battery was formed by charging at a constant current of 0.02C for 60 minutes, at a constant current of 0.05C for 60 minutes, at a constant current of 0.1C for 120 minutes, at a constant current of 0.2C for 180 minutes, heated at 45°C for 24 hours, cooled to room temperature, charged at a constant current of 0.01C and then at a constant voltage until the upper limit voltage of 4.60V was reached, and then charged at a constant voltage of 4.60V until the current dropped to 0.02C. After resting for 10 minutes, the battery was discharged at a constant current of 0.1C until 3V was reached, and then rested for 10 minutes. That is, the battery was cycled at room temperature 4 times in the CC-CV method. (2) At room temperature, charge at a constant current of 1C to 4.60V, then charge at a constant voltage of 4.60V until the current drops to 0.05C, and let stand for 10 minutes; then discharge at a constant current of 1C to 3.0V, and let stand for 10 minutes. (3) Repeat step (2) 400 times, record the discharge capacity of each cycle, calculate the capacity retention rate of the 400th cycle, and obtain the high voltage cycle curve of the solid battery.

[0120] Experimental data The differences in the compounds, initiator content, and compaction density of Examples 1 to 17 and Comparative Examples 1 to 8 of this application are detailed in Table 1.

[0121] Table 1

[0122] The battery performance test details for this application are shown in Table 2.

[0123] Table 2

[0124] By comparing Example 1 with Comparative Examples 1 to 5 and Comparative Example 8, it can be found that the solid electrolyte prepared by the compound in Example 1, whose main chain contains both phosphate ester groups and cyano groups and has a functionality of 6, exhibits superior electrochemical stability, higher ionic conductivity, better electrode wettability, and longer cycle life. The compound in Comparative Example 1 does not contain phosphate ester groups in its main chain, the compound in Comparative Example 2 does not contain cyano groups in its main chain, the compound in Comparative Example 3 contains neither phosphate ester groups nor cyano groups in its main chain, the compound in Comparative Example 4 has a lower functionality, the compound in Comparative Example 5 has a lower functionality, and Comparative Example 8 uses a mixture of compounds containing phosphate ester groups and compounds containing cyano groups, with the phosphate ester groups and cyano groups not on the same molecule; the solid electrolyte prepared by this example does not perform as well as that of Example 1 in all aspects. The reason for this may be that the compound used in Example 1 connects the phosphate ester group and the cyano group to the same molecular backbone through specific carbon atom spacing. The two can work synergistically, forming a stable multi-cyclic complex with transition metal ions through lone pair electrons, effectively anchoring metal ions on the surface of the positive electrode active particles. At the same time, the compound with high functionality can form a complete cross-linked network structure, giving the gel electrolyte suitable mechanical strength and elasticity, and enabling it to adapt to the volume expansion during the charge and discharge process of the electrode. This intramolecular synergy and complete network structure cannot be achieved by the absence of functional groups, reduced functionality, or simple mixing.

[0125] Comparing Examples 1-4 with Comparative Examples 6 and 7 reveals that the solid electrolytes prepared using compounds with appropriate carbon atom spacing between the phosphate ester group and the cyano group in Examples 1-4 exhibit superior electrochemical stability, higher ionic conductivity, better electrode wettability, and longer cycle life. In Comparative Example 6, there is no carbon atom spacing between the phosphate ester group and the cyano group, while in Comparative Example 7, the carbon atom spacing between the phosphate ester group and the cyano group is too large; the solid electrolytes prepared using these compounds show inferior performance compared to Examples 1-4. This may be because the appropriate atomic spacing between the phosphate ester group and the cyano group in the compounds used in Examples 1-4 facilitates the formation of stable multi-cyclic complexes, effectively anchoring transition metal ions and promoting a decrease in the HOMO energy level. The absence of spacer atoms hinders the formation of stable complexes, while excessive spacer atoms result in a loosely structured complex, making it difficult to leverage the synergistic effect of the phosphate ester group and the cyano group.

[0126] Comparing Examples 1 with Examples 8 to 11 reveals that Examples 1 and 10, using prepolymer solutions with compound contents within suitable ranges, produce solid electrolytes with superior electrochemical stability, higher ionic conductivity, better electrode wettability, and longer cycle life. Examples 8 had excessively low compound contents, Examples 9 had relatively low compound contents, and Examples 11 had excessively high compound contents. The solid electrolytes prepared in Examples 1 and 11 were inferior to those in Examples 1 and 10 in terms of electrochemical stability, ionic conductivity, electrode wettability, and cycle life. This may be because the compound contents used in Examples 1 and 10 allow for the formation of a moderately cross-linked network structure, balancing mechanical strength, ionic conductivity, and wettability. When the compound content is too low, the cross-linked network is incomplete and the mechanical strength is insufficient; when the compound content is too high, the cross-linking density is too large and the gel network is too rigid, both of which are detrimental to ionic conductivity and interfacial contact.

[0127] A comparison of Examples 1 and 12 to 15 reveals that Examples 1 and 14, using prepolymer solutions with initiator content within a suitable range, produce solid electrolytes with superior electrochemical stability, higher ionic conductivity, better electrode wettability, and longer cycle life. The initiator content in Example 12 was too low, in Example 13 was relatively low, and in Example 15 was too high; the solid electrolytes prepared using these examples exhibited inferior electrochemical stability, ionic conductivity, and cycle life compared to Examples 1 and 14. This may be because the initiator content used in Examples 1 and 14 allows for a stable polymerization reaction, forming a uniform cross-linked network structure. When the initiator content is too low, the polymerization reaction is incomplete, and the cross-linked network is incomplete; when the initiator content is too high, the polymerization reaction is too fast, and the network structure is uneven, both affecting the overall performance of the gel electrolyte.

[0128] Comparing Examples 1 with Examples 16 and 17 reveals that Examples 1 and 16, using positive electrode sheets with compaction densities within a suitable range, produce secondary batteries with longer cycle lives. Example 16 has a higher compaction density for its positive electrode sheet, while Example 17 has an excessively high compaction density. Although the discharge capacity of the batteries prepared in Example 1 is similar to that of Example 1, the cycle life decreases with increasing compaction density. This may be because, within the compaction density range used in Examples 1 and 16, the solid electrolyte can effectively wet the electrode pores, forming a good ion conduction pathway, and the gel network can adapt to the volume expansion and contraction during electrode charging and discharging. When the compaction density is too high, the electrode pores become too dense, increasing the difficulty of electrolyte wetting and requiring higher mechanical adaptability from the gel electrolyte.

[0129] In summary, Examples 1 to 17 of this application use compounds containing both phosphate ester groups and cyano groups in their main chain with a functionality of 6 to prepare solid electrolytes. By connecting the phosphate ester groups and cyano groups to the same molecular backbone through specific carbon atom spacing, they exert a synergistic effect, forming a multi-cyclic complex capable of anchoring transition metal ions. Simultaneously, by controlling the compound content and initiator content within appropriate ranges, a moderately cross-linked gel network structure with excellent mechanical properties is formed after polymerization. Furthermore, by controlling the compaction density of the positive electrode sheet within an appropriate range, the solid electrolyte can fully wet the electrode pores, adapt to volume expansion during charge and discharge, and effectively suppress oxidative decomposition reactions under high voltage. This improves the wettability, interfacial stability, and chemical stability of solid electrolytes in high-compact, high-voltage lithium cobalt oxide electrodes, significantly enhancing the cycle life of the secondary battery.

[0130] like Figure 2 As shown, Figure 2 The results show the liquid absorption test results of the soft-pack full cells of Example 1 and Comparative Example 1 of this application. From... Figure 2 It can be seen that the liquid absorption of the soft-pack battery corresponding to Example 1 is 8.1g, while the liquid absorption of the soft-pack battery corresponding to Comparative Example 1 is 4.8g. The material structure of Example 1 makes its liquid absorption greater. This shows that the stronger the wetting ability of the electrolyte solution to the battery, the more the specific capacity of the battery active material can be brought into play, which is more beneficial to the battery cycle performance.

[0131] like Figure 3 As shown, Figure 3 These are high-voltage cycling curves of solid-state pouch cells from Embodiment 1 (upper curve) and Comparative Example 1 (lower curve) of this application, wherein... Figure 3 The red curve in the figure is the high-voltage cycling curve of the solid-state pouch cell of Example 1. Figure 3 The black curve in the figure is the high-voltage cycling curve of the solid-state pouch cell in Comparative Example 1. Figure 3 It can be seen that after 400 high-voltage cycles, the solid-state battery corresponding to Example 1 has a capacity that decreases to 92.0% of its original value, while the solid-state battery of Comparative Example 1 has a capacity that decreases to 84.9% of its original value. This shows that the solid electrolyte of Example 1 can withstand higher voltages and has higher voltage stability during the full-cell high-voltage charge-discharge cycle, and can still maintain the normal operation of the battery, thereby improving the battery cycle life.

[0132] The embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A compound, characterized in that, The compound comprises a molecular structure as shown in Formula I: Equation I; Where n1, n2, and n3 are each an independent integer from 1 to 3; R1, R2, R3, R4, R5, and R6 are each independently selected from the groups shown in Formula II: Formula II, m takes the value of an integer from 1 to 3. Indicates the connection site; R7 is selected from H or methyl.

2. The compound according to claim 1, characterized in that, The compound is selected from one or more of the following chemical formulas: 。 3. A phosphate ester-based polymer, characterized in that, The compounds that polymerize to form the phosphate-based polymer include those as described in claim 1 or 2.

4. A prepolymer liquid, characterized in that, The prepolymer solution comprises a lithium salt, a solvent, and a polymer monomer, wherein the polymer monomer has a molecular structure as shown in Formula I: Equation I; Where n1, n2, and n3 are each an independent integer from 1 to 3; R1, R2, R3, R4, R5, and R6 are each independently selected from the groups shown in Formula II: Formula II, m takes the value of an integer from 1 to 3. Indicates the connection site; R7 is selected from H or methyl.

5. The prepolymer liquid according to claim 4, characterized in that, The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium difluorophosphate; and / or The solvent includes at least one of carbonate solvents and carboxylic acid ester solvents.

6. The prepolymer liquid according to claim 4, characterized in that, The prepolymer solution also includes an initiator and / or additives; The additives include at least one selected from propane sulpholactone, vinyl sulfate, and 1,3,6-hexanetrionitrile; and / or The initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and azobiscyclohexylformitrile.

7. The prepolymer liquid according to claim 6, characterized in that, The polymer monomer constitutes a mass fraction of 1% to 5% of the prepolymer solution; and / or The lithium salt constitutes 10% to 20% of the mass fraction of the prepolymer solution; and / or The solvent accounts for 75% to 87% of the mass fraction of the prepolymer solution; and / or The additive constitutes 1% to 5% of the prepolymer solution by mass; and / or The mass ratio of the initiator to the polymer monomer is 0.003 to 0.

03.

8. A solid electrolyte, characterized in that, The solid electrolyte is formed by curing a prepolymer liquid as described in any one of claims 4 to 7.

9. A secondary battery, characterized in that, The secondary battery includes: Positive electrode sheet; Negative electrode sheet and A solid electrolyte located between the positive electrode and the negative electrode, the solid electrolyte being formed by curing a prepolymer liquid as described in any one of claims 4 to 7.

10. The secondary battery according to claim 9, characterized in that, The positive electrode includes lithium cobalt oxide.

11. The secondary battery according to claim 9, characterized in that, The compaction density of the positive electrode sheet ranges from 4.1 g / cm³. 3 Up to 4.4 g / cm 3 .

12. An electrical appliance, characterized in that, The electrical device includes the solid electrolyte as described in claim 8, or the secondary battery as described in any one of claims 9 to 11.

Citation Information

Patent Citations

  • Adsorption promoter for photosensitive weld retarding agent

    CN1077470A

  • Anti-static photocuring monomer, preparation method thereof and anti-static photocuring coating

    CN111892836A